Pembrolizumab-Associated Cardiotoxicity: A Retrospective Analysis of the FDA Adverse Events Reporting System - Stefan Milutinovic; Predrag Jancic; Vera Jokic; Marija Petrovic; Igor Dumic; Ambar Morales Rodriguez; Nikola Tanasijevic; Dustin Begosh-Mayne; Dragana Stanojevic; Ricardo O. Escarcega; Juan Lopez-Mattei; Xiangkun Cao (MDPI AG, 2024)
Background: Immune checkpoint inhibitors (ICIs) have been successfully used in the previous decade for the treatment of a variety of malignancies. Adverse events (AEs) can cause many symptoms, most notably cardiac. We analyzed the frequency of these adverse events, comparing pembrolizumab and other ICIs. Methods: Using the Food and Drug Administration (FDA) adverse event reporting database (FAERS), we searched for all adverse events of interest reported for every ICI included in this study. After obtaining the data, we conducted a disproportionality analysis using the reporting odds ratio (ROR) and the information component (IC). Results: A total of 6719 ICI-related cardiac adverse events of interest were reported in the database. Serious outcomes were reported in 100% of the cases, with 34.3% of the cases ending fatally. Compared with all other medications in the database, pembrolizumab use was more frequently associated with myocarditis, pericardial disease, heart failure, and atrial fibrillation. No difference was found in cardiotoxicity between different ICIs. Conclusions: Although infrequent, cardiac AEs in pembrolizumab use are associated with serious outcomes and high mortality. Prospective studies are needed to further research the connection between ICI use and cardiotoxicity.